2016
DOI: 10.1302/2046-3758.54.2000578
|View full text |Cite
|
Sign up to set email alerts
|

An international survey to identify the intrinsic and extrinsic factors of research studies most likely to change orthopaedic practice

Abstract: ObjectivesEvidence -based medicine (EBM) is designed to inform clinical decision-making within all medical specialties, including orthopaedic surgery. We recently published a pilot survey of the Canadian Orthopaedic Association (COA) membership and demonstrated that the adoption of EBM principles is variable among Canadian orthopaedic surgeons. The objective of this study was to conduct a broader international survey of orthopaedic surgeons to identify characteristics of research studies perceived as being mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
(51 reference statements)
1
5
0
Order By: Relevance
“…As part of a skin closure trial, we believe that randomisation is essential to influence surgeons in changing their practice. This has also been shown previously with 94% of surgeons stating that randomisation is essential in the design of a trial that would change their current practice …”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…As part of a skin closure trial, we believe that randomisation is essential to influence surgeons in changing their practice. This has also been shown previously with 94% of surgeons stating that randomisation is essential in the design of a trial that would change their current practice …”
Section: Discussionsupporting
confidence: 67%
“…This has also been shown previously with 94% of surgeons stating that randomisation is essential in the design of a trial that would change their current practice. 4 In a 3-armed trial comparing clips, subcuticular sutures and barbed sutures for skin closure in 278 hip and knee arthroplasty surgeries found that skin wounds closed using sutures were significantly more likely to have complications than staples (P = .033). 5 There was also a significant difference in complications between staples and barbed sutures (P = .017).…”
Section: Discussionmentioning
confidence: 99%
“…2 3 4 5 Medical journals also use the same measures to define their impact in an attempt to attract a greater number of high-quality authors. 3 , 6 , 7 For academic orthopaedic departments, publication productivity is extremely important when attracting high-quality researchers and extramural funding. 8 Stavrakis et al 8 have shown that departmental productivity was closely correlated with leadership productivity and funding.…”
mentioning
confidence: 99%
“…Recent evidence suggests that orthopaedic surgeons do consider JIF to be important when making clinical decisions. 17 , 18 Therefore, the potential for citation skew could undermine this process. If citation skew does indeed exist in the orthopaedic literature, then these clinical decisions could be considered to be based on injudicious information.…”
mentioning
confidence: 99%